Monitoring the agri-food system in Myanmar: Rice millers – August 2023 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
In August 2023, we surveyed 388 active rice millers from 13 states and regions across Myanmar to learn more about the impacts of the current political and COVID-19 crises. This report presents the key results and analysis from those interviews. Key findings • Patterns of reported business disruptions show substantial improvements compared to a year ago, but limited changes since March 2023. Access to electricity remained the most common disruption and was reported to be the biggest challenge by more than half of the sample. Fuel cost, fuel access, and transportation costs were also common disruptions although they are far less common than in August 2022. • Larger mills mostly use electricity and are therefore most impacted by the persistent electrical supply issues. Yet some have expanded their power sources in the past three years by investing in electricity generators powered by husks or fuel. • Despite the challenges, milling throughput in 2023 is similar to 2022. However, paddy and rice storage volumes are significantly lower this year, while conditional average amount of credit provided to farmers increased significantly during the 2023 monsoon season. • Paddy and rice prices continued their rapid upward trajectory that began in mid-2022 and in August were 80 percent higher than one year prior and 2.5 times the price from 2021. The local Myanmar price changes are largely driven by global rice markets and foreign exchange rates. Looking forward • Recent policies to keep consumer rice prices low – including efforts to control rice prices and to limit export licensing – along with erratic foreign exchange policies can lead to increased price volatility and uncertainty for farmers, traders, millers, and exporters. If domestic paddy and rice prices fall because of these interventions, millers and farmers are less likely to recover investment costs, pay off debts, and make profits for further investment in next year’s productions.